JENIS-JENIS TINDAK TUTUR ILOKUSI GURU BAHASA INDONESIA DALAM PEMBELAJARAN MEMBACA CERITA FABEL DI KELAS VII SMPN 11 KOTA JAMBI TAHUN AJARAN 2017/2018 - Dea Romesi; Ade Rahima; Firman Tara (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this research to describe the types of ilocutionary act that the Indonesian language teacher use in giving fable story lesson towards students class VII SMP Negeri 11 Kota Jambi Academic Year 2017/2018. This research is descriptive qualitative. The technique of collecting data is observation, recording, and note-taking. The data then is analyzed by using pragmatic analysis. Based on the result of the analysis, it can be found that there 4 types of ilocutionary act that is used by the Indonesian language teacher, they are (1) directive, (2) declarative, (3) insertive, (4) expressive. The functions of teacher’s ilocutionary act is really important to the students in learning process. In addition, it is recommended to the teacher to improve their expressive utterance in order to increase studeents willinngness in learning and to reduce the use of directive utterance so that the students will not bored in studying the lesson.Key Word: ilocutionary, pragmatic